2018
DOI: 10.1371/journal.pone.0193431
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors of extensively drug-resistant Pseudomonas aeruginosa infections

Abstract: BackgroundThe incidence of nosocomial infections from extensively drug-resistant Pseudomonas aeruginosa (XDR-PA) has been increasing worldwide. We investigated the prevalence and factors associated with XDR-PA infections, including the factors that predict mortality.MethodsWe retrospectively studied a cohort of adult, hospitalized patients with P. aeruginosa (PA) infections between April and December 2014.ResultsOf the 255 patients with PA infections, 56 (22%) were due to XDR-PA, 32 (12.5%) to multidrug resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 33 publications
5
43
2
2
Order By: Relevance
“…However, this rate is lower than the rates reported by Katvoravutthichai (21,26,27). The prevalence of XDR strains (5%) in our study was lower than that reported by Palavutitotai et al (2018) in Thailand (22%) (28). We found no significant association between source of isolation and antibiotic resistance, but the frequency of MDR strains was highest in blood specimens.…”
Section: Discussioncontrasting
confidence: 80%
“…However, this rate is lower than the rates reported by Katvoravutthichai (21,26,27). The prevalence of XDR strains (5%) in our study was lower than that reported by Palavutitotai et al (2018) in Thailand (22%) (28). We found no significant association between source of isolation and antibiotic resistance, but the frequency of MDR strains was highest in blood specimens.…”
Section: Discussioncontrasting
confidence: 80%
“…Another Spanish study [33] focused on BSIs in solid organ transplant recipients identified a higher mortality rate for patients with bacteremia due to XDR P. aeruginosa (n = 31) compared to those with BSI caused by other microorganisms (n = 287), and it was found to be an independent risk factor for mortality (20/22 studied strains showed the ST175 pattern). Other studies [34,35] have addressed the impact of XDR strains on different sources of infection, not exclusively in bacteremia. For instance, a Thai study of 255 patients with P. aeruginosa infections, including 56 XDR strains, found that an XDR phenotype was an independent factor of mortality attributable to infection when compared to non-XDR isolates [34].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [34,35] have addressed the impact of XDR strains on different sources of infection, not exclusively in bacteremia. For instance, a Thai study of 255 patients with P. aeruginosa infections, including 56 XDR strains, found that an XDR phenotype was an independent factor of mortality attributable to infection when compared to non-XDR isolates [34]. Samonis et al found the same association with mortality in a cohort of 89 P. aeruginosa infections (52 of them with bacteremia and 22 XDR isolates) in cancer patients in Greece [35].…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the antimicrobial susceptibility patterns of isolates is needed if we are to decrease the risk of the spread of resistant P. aeruginosa strains [10]. Ongoing microbiological surveillance has been recommended by the World Health Organization (WHO), to improve infection control measures especially in the healthcare setting and to guide the physicians in the choice of empirical or directed treatment [11].…”
Section: Introductionmentioning
confidence: 99%